STRUKTUR MODEL PEMBELAJARAN PEGAWAI YANG BERPENGARUH TERHADAP KINERJA ORGANISASI ( KAJIAN PADA KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK JAKARTA KHUSUS) - Muhammad Na'im Amali (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2015)
Due to its strategic role, regional Office of the DGT of special jakarta is required to be able to improve its performance by improving its employees’ capabilities through sustainable learning process as part of the taxation administration reform continuosly made. This study aims to describe the learning process in the regional Office of DGT of special Jakarta ; to analyze the relationships of the stucture of the employee learning model contructed of the self-directed learning in the workplace, the process of the transformation into the organizational learning form, the knowledge management application, the innovation creation in the context of the learning organization in order to improve the organizational performance ; and to analyze whether or not there is diffrence in the structure of the employee learning model among tax office units and among groups of emloyees.